Oficinas terapêuticas em saúde mental: um estudo sobre as concepções de coordenadores - Oliveira, Ana Luiza de Mendonça (2018)
The therapeutic workshops aim, above all, at the social (re)insertion and the promotion of the autonomy of people in psychic suffering through the development of diverse collective practices, oriented, basically, to creative expression, to the learning of professional activities or to literacy. In this way, therapeutic workshops appear as one of the main treatment devices offered in Psychosocial Care Centers (CAPSs). The present study aimed to understand the conceptions of professionals who coordinate therapeutic workshops in CAPSs regarding such intervention tool. For that, we conducted semi- structured interviews with twelve professionals who coordinated therapeutic workshops in CAPSs of a city in the interior of the State of Minas Gerais. Participants were interviewed individually, at the dependences of the CAPSs where they worked, at agreed times. In addition, a field diary was used to record observations and experiences related to interviews. The interviews were recorded in audio and later transcribed. The treatment of the data was undertaken from the thematic content analysis, which consists of a set of techniques aimed at the interpretation of various forms of discourse. Three categories were configured: 1) Conceptions about basic aspects of therapeutic workshops, 2) Conceptions about (non) adherence to therapeutic workshops, and 3) Conceptions about indication criteria and benefits of therapeutic workshops. The first category was divided into three subcategories, covering conceptions of: a) the therapeutic value of therapeutic workshops, b) the objectives of therapeutic workshops, and c) the specificities of the different modalities of therapeutic workshops. There was no consensus on the therapeutic value of therapeutic workshops. But in line with the conceptions of several participants, therapeutic workshops should have as their basic purpose the social (re)insertion of users and necessarily involve the production of something material, concrete. It was also found that, for participants in general, the limits between the different modalities of therapeutic workshops are unclear. Regarding the second category, the results evidenced the predominance of a conception according to which both adherence and non-adherence of users to therapeutic workshops are determined by factors related only to their own, and not to the activities performed in the therapeutic workshops or to the coordination. In addition, gender differences were also pointed out as relevant in this regard. The results concerning the third category showed that, according to the conception of the majority of the participants, there are no indication criteria to be adopted, and the coordinator of a therapeutic workshop should only indiscriminately invite the users of the service to attend it. And the benefits of therapeutic workshops would be reduced, basically, to socialization, mutual support between users and occupancy of their time. The results evidenced the need for new research on the subject, so that it can be verified whether, in other contexts, the scenario presented is similar or not. New research may also be considered relevant for judging by the threats of setbacks and loss of rights associated with recent changes in mental health policy, which, contrary to the antimanicomial clinic, encourage the rescue of the “old Psychiatry”.